The National Center for Effective Schools: Extending Knowledge and Practice of School Improvement - Edie L Holcomb; Kent D. Peterson (Educational Considerations, 1991)
The structure and the programs of school improvement must constantly be reassessed and extended to take into consideration new knowledge and new practices that can serve school improvement.